Dirty pooling and polluted purchase. (2015) - Sy, Aida; Tinker, Tony; Briloff, Abraham
It speaks to the credit of our dear friend, Abe Briloff, now departed, that his works continues to resonate with financial debacles that we continue to witness today. His mode of analysis is instructive to all students and scholars as to how to dissect financial failures, past and present. It is to Abe's endless credit that his work was conducted while for the past 50 years, he has been clinically blind.